If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12.88 + -0.88(x + 0.5) = 0.25 + 2(x + -3.17) Reorder the terms: 12.88 + -0.88(0.5 + x) = 0.25 + 2(x + -3.17) 12.88 + (0.5 * -0.88 + x * -0.88) = 0.25 + 2(x + -3.17) 12.88 + (-0.44 + -0.88x) = 0.25 + 2(x + -3.17) Combine like terms: 12.88 + -0.44 = 12.44 12.44 + -0.88x = 0.25 + 2(x + -3.17) Reorder the terms: 12.44 + -0.88x = 0.25 + 2(-3.17 + x) 12.44 + -0.88x = 0.25 + (-3.17 * 2 + x * 2) 12.44 + -0.88x = 0.25 + (-6.34 + 2x) Combine like terms: 0.25 + -6.34 = -6.09 12.44 + -0.88x = -6.09 + 2x Solving 12.44 + -0.88x = -6.09 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12.44 + -0.88x + -2x = -6.09 + 2x + -2x Combine like terms: -0.88x + -2x = -2.88x 12.44 + -2.88x = -6.09 + 2x + -2x Combine like terms: 2x + -2x = 0 12.44 + -2.88x = -6.09 + 0 12.44 + -2.88x = -6.09 Add '-12.44' to each side of the equation. 12.44 + -12.44 + -2.88x = -6.09 + -12.44 Combine like terms: 12.44 + -12.44 = 0.00 0.00 + -2.88x = -6.09 + -12.44 -2.88x = -6.09 + -12.44 Combine like terms: -6.09 + -12.44 = -18.53 -2.88x = -18.53 Divide each side by '-2.88'. x = 6.434027778 Simplifying x = 6.434027778
| 4x+5y+6x-3x+3y= | | https://content.grantham.edu/at/MA105/exams/w2_10.jpg | | 4=60 | | 7+4x=7x+40 | | 2k+-1=2+k | | X^4+11=35 | | 18+7x-9=-27+3x | | -10=(1/4)(8y-12) | | -1x+0.33=0.25 | | 50b+36c= | | x+12=-(13) | | 50b+3c= | | 9+3(3x+5)=24+9x | | 50b+3= | | 60/p=4;15,16,17 | | 1/2x5/4 | | 2(14)-x+8=0 | | x/-7=(-5) | | -5x+13=-15 | | z+2=z | | 8b+10b+2+3b= | | s=6r^3(s/6r^3) | | -10+6x=3x-4 | | X/48=5/6 | | 7x+5=-5x | | 9(x+2)-7=2x+11 | | 0.25y=2/3-6 | | 1=-2x+16 | | 6.4*8.4=52.08 | | y=-2(1)+16 | | X^2+8y+2x-23=0 | | 0=-16t^2+128t+30 |